P099 Postprandial intestinal motility and related physiology in active small-bowel Crohn's disease. (16th January 2018) - Khalaf, A; Hoad, C L; Menys, A; Radford, S; Nowak, A; Paparo, S; Lingaya, M; Falcone, Y; Singh, G; Taylor, S A; Spiller, R C; Gowland, P A; et al.
Abstract: Background: Magnetic Resonance Imaging (MRI) of small-bowel motility in Crohn's disease (CD) is a sensitive disease activity biomarker and linked to patient symptoms1. Intestinal inflammation is associated with an increase in Polypeptide YY (PYY), Glucagon-like peptide 1 (GLP-1) and cholecystokinin (CCK)2. These peptides have a negative effect on intestinal motility. Our aim was to assess gut peptide, small-bowel motility, and patient symptom response to a standard test meal to better characterise intestinal physiology. Methods: Participants underwent baseline and postprandial MRI scans, symptom questionnaires, and blood sampling (GLP-1, PYY, and CCK) at intervals for 270 min following a test meal: soup (400 g) (chicken or mushroom) (Heinz, Wigan, UK); (kcal) 51, protein 1.5 g, carbohydrate 4.7 g, fat 2.9 g per 100 g. Supine MRI scans were performed using a 1.5 T Philips Achieva MRI scanner. Gastric volume, gall bladder volume, small-bowel water content (SBWC) and small-bowel motility were assessed using MRI. Patients also underwent a standard contrast enhanced clinical MR enterography (MRE) and the MaRIA score applied to quantify disease activity. This study was approved by the Nottingham Research Ethics Committee. All participants gave informed written consent. Trial registration number: NCT03052465. Data are presented as mean ± SEM. Results: Sixteen CD patients with active small-bowel disease (Harvey–Bradshaw index 4.9 ± 1.3, C-reactive protein 10.0 ± 4.0 mg/dl, faecal calprotectin 796.4 ± 173.0 µg/g and MaRIA score 21.7 ± 1.8) and 20 age-, BMI- and gender-matched healthy volunteers (HV) were recruited. CD patients showed a significantly ( p ≤ 0.05) slower fasting small-bowel motility (50 ± 6 a.u.) compared with HV (77 ± 10 a.u.). Postprandial SBWC was significantly greater in CD than HV (measured as area under the curve CD: 18452, HV: 13760, p ≤ 0.05). Fasting PYY (CD: 236 ± 16 pg/ml, HV: 118 ± 11 pg/ml, p ≤ 0.0001) and GLP-1 (CD: 50 ± 8 µg/ml HV: 13 ± 3 µg/ml, p ≤ 0.0001) were significantly higher in CD compared with HV with this difference persisting at each time point of the study ( p ≤ 0.0001). The meal induced a significant increase ( p ≤ 0.0001) in fullness, bloating, and abdominal pain scores in patients (28 ± 4, 22 ± 3, and 12 ± 2 mm, respectively) compared with HV (12 ± 4, 3 ± 3, and 1 ± 2 mm, respectively). No differences were noted in gastric volumes, GB volume, CCK concentration, and postprandial motility. Conclusions: The fasting hypomotility noted in CD may be ascribed to the increased fasting GI peptides. An increase postprandial SBWC and postprandial symptoms has been observed in CD. We plan to replicate these pilot data in a larger cohort with the aim of identifying key biomarkers for pharmacological modulation to improve patient symptoms. References: 1. Menys A. Aberrant motility in unaffected small bowel is linked to inflammatory burden and patient symptoms in Crohn's disease. Inflamm. Bowel Dis., 2016;22:424–32. 2. Moran GW. Crohn's disease affecting the small bowel is associated with reduced appetite and elevated levels of circulating gut peptides. Clin Nutrition, 2013;32:404–11.